The first swallow of the East (Zien Journal of Social Sciences and Humanities, 2022)
This article covers the life and work of Tamara, an artist who has left an indelible mark on Uzbek art and culture. At the same time, there was talk of large-scale reforms aimed at developing the activities of the Tamarahonim House Museum.